Review. Fulvio Bertuccelli, The Socialist Movement in Turkey (1960-1971). Ideology and politics between two coups, Rome, Aracne, 2023. (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
.
Keywords: Socialist Movement; Turkey; Ideology; Rome; Aracne